Pemanfaatan Metode Mind Mapping dalam Meningkatkan Minat Belajar Pendidikan Agama Islam Siswa Kelas IV SD Muhammadiyah 1 Bontang - Sandratika, Kamelia; Syamsiar, Syamsiar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research aims to determine the benefits of the digital Mind Mapping method in increasing interest in learning Islamic religious education in class IV students at SD Muhammadiyah 1 Bontang. Utilizing the digital Mind Mapping Method, the easiest way to put information into the brain and take information out of the brain, can also be categorized as a creative note-taking technique. The method used is qualitative. Data collection techniques are observation, interviews and documentation. The research results show that there are differences in students' enthusiasm in their interest in learning Islamic religious education material using the lecture method and Mind Mapping in the application. It can be concluded that digital mind mapping helps students understand the concepts of Islamic religious education better, students are more involved and active in the learning process. Students find it easier to access and manage information and increase their interest in learning.